Characteristics of APS and VPS plasma spray processes - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Plasma is an electrically conductive gas containing ions, electrons and neutral molecules. This state of matter is created by an electrical discharge and can be maintained at steady state by introducing alternating or direct current. The paper describes the structure of plasma, the thermodynamic characteristics and a method of creating plasma that allow the application of plasma as a source of energy for plasma spray processes. In general, all existing materials in a form of powder may be deposited by plasma coating on the surfaces of various materials. At high temperatures, powder material particles are introduced into a conductive plasma gas, melting and accelerating to the substrate to form coatings. The wide use of plasma spray coatings in all industrial areas is of particular importance, because different combinations of surface layers can significantly increase the resistance of machine parts to: wear, abrasion, erosion, cavitation, corrosion and fatigue resistance at low and elevated temperatures with increased resource and reliability of the parts in service.